Catalysis with chalcogen bonds: neutral benzodiselenazole scaffolds with high-precision selenium donors of variable strength. Issue 12 (16th October 2017) - Benz, Sebastian; Mareda, Jiri; Besnard, Céline; Sakai, Naomi; Matile, Stefan
Abstract : Benzodiselenazoles are introduced for efficient anion binding and unprecedented non-covalent catalysis in the focal point of neutral selenium-based chalcogen-bond donors. Abstract : The benzodiselenazoles (BDS) introduced in this report fulfill, for the first time, all the prerequisites for non-covalent high-precision chalcogen-bonding catalysis in the focal point of conformationally immobilized σ holes on strong selenium donors in a neutral scaffold. Rational bite-angle adjustment to the long Se–C bonds was the key for BDS design. For the unprecedented BDS motif, synthesis of 12 analogs from o -xylene, crystal structure, σ hole variation strategies, optoelectronic properties, theoretical and experimental anion binding as well as catalytic activity are reported. Chloride binding increases with the depth of the σ holes down to K D = 11 μM in THF. Catalytic activities follow the same trend and culminate in rate enhancements for transfer hydrogenation of quinolines beyond 100 000.